Evaluation of fruit quality parameters of Rosa taxa from the Carpathian basin - Kovács, Sz.; G. Tóth, M.; Facsar, G. (International Journal of Horticultural Science, 2004)
From the wide range of genetic sources available in Hungary, we have chosen as objective the evaluation of those rose taxa, which — on the base of their quality and morphologic features — are suitable for selecting fruit production varieties or parent varieties for further breeding. We examined physical and inner parameters of fruits of Rosa taxa, and evaluated the correlations by mathematical statistic methods. Namely, if a correlation can be found between physical and inner parameters, fruit production value can be determined by less examinations in the future. According to our results, there is a large variability in some physical parameters (weight, diameter of fruits; weight, number of achenes) as well as in inner content values (vitamin C, glucose, fructose, K, Ca, Fe, Zn and Cu content) of rosehip, regarding production year, habitat and even the individual of examination. Twice as much ascorbic acid can be found in achene-free fruits, and nearly five times as much in their dry product as in fresh whole fruits. It was established repeatedly, that vitamin C concentrates in fruit flesh, and ascorbic acid content can be preserved better in achene-free flesh. There is no essential difference in citric acid and carbo-hydrate content of whole and achene-free rosehips. However, macro- and microelement content of whole fruits is 30-40% higher than that of achene-free fruit flesh. The connection between fresh weight and diameter, as well as achene number and seed weight of fruits can be described by the function y=axb. A significant relationship can be found in case of K-Fe, Ca-Mg, Ca-B, Ca-Mn and Zn-Cu, between fresh weight and B content of fruits. According to our examinations, fresh weight of rose species with a higher citric acid content is usually higher, while their Fe content is smaller. Glucose content of fruits of rose species is directly proportional to their Ca and Zn contents. Zn content of rose species with higher fructose content is usually smaller.